2007
DOI: 10.1097/bsd.0b013e31802f80c8
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cervical Microdiscectomy With or Without Fusion

Abstract: ACD technique offers satisfactory outcome regardless of whether fusion process is applied or not. Fusion with semirigid plate offers an advantage at operated level in immediate postoperative period in regard of disc height and neural foramen height. However, semirigid anterior plates by definition do not stop subsidence and the advantage that is offered by this technique is not persistent. On the other hand, to apply fusion process with semirigid plate system offers significantly less narrowing in disc height … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 22 publications
0
35
0
2
Order By: Relevance
“…There was also moderate evidence that pain relief after 6 weeks was higher after ACDF, but that return-to-work was higher after ACD after the same time period. 14 Oktenoglu et al 22 and Xie and Hurlbert 40 both reported Class II studies comparing ACD to ACDF. The Oktenoglu et al 22 study randomized 20 patients by coin flip: 11 patients were assigned to ACD and 9 to ACDF.…”
Section: Scientific Foundationmentioning
confidence: 99%
See 2 more Smart Citations
“…There was also moderate evidence that pain relief after 6 weeks was higher after ACDF, but that return-to-work was higher after ACD after the same time period. 14 Oktenoglu et al 22 and Xie and Hurlbert 40 both reported Class II studies comparing ACD to ACDF. The Oktenoglu et al 22 study randomized 20 patients by coin flip: 11 patients were assigned to ACD and 9 to ACDF.…”
Section: Scientific Foundationmentioning
confidence: 99%
“…14 Oktenoglu et al 22 and Xie and Hurlbert 40 both reported Class II studies comparing ACD to ACDF. The Oktenoglu et al 22 study randomized 20 patients by coin flip: 11 patients were assigned to ACD and 9 to ACDF. Outcomes were assessed using the VAS at 1 day and 12 months after surgery by a blinded observer.…”
Section: Scientific Foundationmentioning
confidence: 99%
See 1 more Smart Citation
“…Yazarlar sonuç olarak, plaksız anterior diskektomi yöntemi-nin de tatminkâr klinik iyileşme sağladığı sonucuna varmışlardır. [21] Olgu Otuz dört yaşında kadın hasta, bir aydır devam eden şiddetli boyun ve her iki kola yayılan ağrı yakınmasıyla kliniğimize başvurdu. Ağrının akut baş-langıçlı olduğunu ifade ediyordu.…”
Section: Bt Miyelografiunclassified
“…[17] Öktenoğlu ve arkadaşları, sadece anterior diskektomi ve enstrümanla füzyon uygulanan (anterior plak vida sistemi) olguların klinik ve radyolojik sonuçlarını karşılaştırmayı amaçlayan, randomize ileriye dönük bir çalışma tasarlamışlardır. [21] Olgu sayısı 20'dir ve görece az olarak nitelendirilebilir. Ancak, iki hafta süreklilik arzeden ya da girişimsel tedaviye yanıt vermeyen olgular çalışmaya dahil edilmişlerdir.…”
Section: Bt Miyelografiunclassified